Leptin produced by obese adipose stromal/stem cells enhances proliferation and metastasis of estrogen receptor positive breast cancers. Issue 1 (December 2015) - Strong, Amy; Ohlstein, Jason; Biagas, Brandi; Rhodes, Lyndsay; Pei, Dorothy; Tucker, H.; Llamas, Claire; Bowles, Annie; Dutreil, Maria; Zhang, Shijia; Gimble, Jeffrey; Burow, Matthew; et al.
Abstract Introduction The steady increase in the incidence of obesity among adults has been paralleled with higher levels of obesity-associated breast cancer. While recent studies have suggested that adipose stromal/stem cells (ASCs) isolated from obese women enhance tumorigenicity, the mechanism(s) by which this occurs remains undefined. Evidence suggests that increased adiposity results in increased leptin secretion from adipose tissue, which has been shown to increased cancer cell proliferation. Previously, our group demonstrated that ASCs isolated from obese women (obASCs) also express higher levels of leptin relative to ASCs isolated from lean women (lnASCs) and that this obASC-derived leptin may account for enhanced breast cancer cell growth. The current study investigates the impact of inhibiting leptin expression in lnASCs and obASCs on breast cancer cell (BCC) growth and progression. Methods Estrogen receptor positive (ER+) BCCs were co-cultured with leptin shRNA lnASCs or leptin shRNA obASCs and changes in the proliferation, migration, invasion, and gene expression of BCCs were investigated. To assess the direct impact of leptin inhibition in obASCs on BCC proliferation, MCF7 cells were injected alone or mixed with control shRNA obASCs or leptin shRNA obASCs into SCID/beige mice. Results ER+ BCCs were responsive to obASCs during direct co-culture, whereas lnASCs were unable to increase ER+ BCC growth. shRNA silencing of leptin in obASCs negated the enhanced proliferative effects of obASC on BCCs following direct co-culture. BCCs co-cultured with obASCs demonstrated enhanced expression of epithelial-to-mesenchymal transition (EMT) and metastasis genes (SERPINE1, MMP-2, and IL-6), while BCCs co-cultured with leptin shRNA obASCs did not display similar levels of gene induction. Knockdown of leptin significantly reduced tumor volume and decreased the number of metastatic lesions to the lung and liver. These results correlated with reduced expression of both SERPINE1 and MMP-2 in tumors formed with MCF7 cells mixed with leptin shRNA obASCs, when compared to tumors formed with MCF7 cells mixed with control shRNA obASCs. Conclusion This study provides mechanistic insight as to how obesity enhances the proliferation and metastasis of breast cancer cells; specifically, obASC-derived leptin contributes to the aggressiveness of breast cancer in obese women.